2012
DOI: 10.1128/jvi.05493-11
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Bacitracin on Human Papillomavirus Type 16 Infection: Enhancement of Binding and Entry and Inhibition of Endosomal Penetration

Abstract: e Cell invasion by human papillomavirus type 16 (HPV16) is a complex process relying on multiple host cell factors. Here we describe an investigation into the role of cellular protein disulfide isomerases (PDIs) by studying the effects of the commonly used PDI inhibitor bacitracin on HPV16 infection. Bacitracin caused an unusual time-dependent opposing effect on viral infection. Enhanced cellular binding and entry were observed at early times of infection, while inhibition was observed at later times postentry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 82 publications
(108 reference statements)
2
47
0
Order By: Relevance
“…1D) suggests that the viral genome may traffic from the Golgi to the ER during entry. It was previously reported that HPV16 infection was inhibited by Brefeldin A, which affects several trafficking steps including ER entry and by knock-down of protein disulfide isomerases that are primarily localized in the ER (11,42). The enrichment of potassium channels in our list of hits suggests that the channels themselves or ion fluxes play a role in infection.…”
Section: Discussionmentioning
confidence: 76%
“…1D) suggests that the viral genome may traffic from the Golgi to the ER during entry. It was previously reported that HPV16 infection was inhibited by Brefeldin A, which affects several trafficking steps including ER entry and by knock-down of protein disulfide isomerases that are primarily localized in the ER (11,42). The enrichment of potassium channels in our list of hits suggests that the channels themselves or ion fluxes play a role in infection.…”
Section: Discussionmentioning
confidence: 76%
“…In pestiviruses, scission of disulfide bonds in the envelope glycoproteins is thought to activate the virion for fusion, as the combination of reducing agent and low pH allows fusion with the plasma membrane ("fusion from without"), albeit at low efficiency (6). A potential precedent is human papillomavirus, which requires a cellular protein disulfide isomerase in addition to low endosomal pH for disassembly of the disulfide-linked capsid and delivery of viral DNA into the cytoplasm (14).…”
mentioning
confidence: 99%
“…2B). The HD mutation had no obvious effect on virion binding, entry, or time-dependent exposure of the buried L1-7 epitope, a marker for uncoating (44,48) (Fig. 2C).…”
Section: Resultsmentioning
confidence: 98%
“…293TT, HeLa, and HaCaT cells were maintained as previously described (44). Cloning of mutant viruses was achieved by site-directed mutagenesis of the L1/L2 expression plasmid pXULL using a QuikChange-XL II system (catalog number 200521; Agilent), and all mutant plasmids were verified by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation